Предмет: Алгебра,
автор: fox3929
Помогите прошу пожалуйста
Приложения:
Ответы
Автор ответа:
1
Формулы , которые можно использовать ,для упрощения :
(a-b)²=a²+2ab+b² , (a-b)×(a+b)=(a²-b²)
(x-7)^2+3 = (x-2)(x+2)
(x²-14x+49)+3 = x²-4
x²-14x - x² = -4-3-49
-14x=-56
14x=56
x=56÷14
x=4
Ответ : 4
Похожие вопросы
Предмет: Алгебра,
автор: sjdhshsiaj
Предмет: Английский язык,
автор: alenkazerenkova
Предмет: Математика,
автор: daianakoishi
Предмет: Литература,
автор: кэти51
Предмет: Математика,
автор: Оксаночкамоя